Social Security Number Holders in the United States, 1909-2019 - Ogihara, Yuji (Frontiers in Big Data, 2021)
Currently, a social security number (SSN) is held by almost every legal resident of the United States and works as an important numbering system. However, this was not the case in the early years of the Social Security program and historical changes in SSN holder rates had not been examined sufficiently. It is important to understand the changes in health policies and situations. Thus, the present article examined historical changes in the rates of SSN holders in the United States between 1909 and 2019. Analyses demonstrated that the rates clearly increased. Specifically, in Phase 1 (1909-1919), the rates were low in the early period, but they increased markedly. In Phase 2 (1919-1952), the rates continued to increase gradually. In Phase 3 (1952-2019), the rates were almost 100% and reached saturation. This basic information leads to a better understanding of the health policies and situations, contributing to medical and social science research.